Malignant transformation of hepatocellular adenoma - Sempoux, Christine (Hepat Oncol, 2014)
Hepatocellular adenomas carry a risk of malignant transformation. However, little is known about the rate of this risk, the predisposing factors, the histological and/or immunohistochemical markers and the precursor lesions. Even the pathogenesis of malignant transformation itself is poorly understood. This review details the current knowledge on the subject.